An assessment of accessibility to social welfare services of the Department of Social Development : the case study of Shakung Village, Limpopo Province, South Africa - Maluleke, Enoch (My University, 2021)
The aim of the study was to assess the implementation of accessibility of social welfare services of the Department of Social Development in Shakung Village, Limpopo province. The objectives of the study were to examine the effectiveness of the implementation on the accessibility of social welfare services by the Department of Social Development, investigate challenges of the implementation on the accessibility of social welfare services by the Department of Social Development and assess the access level that beneficiaries have on social welfare services in the Shakung Village in Limpopo province, South Africa. The study was qualitative and the researcher used a case study research design. The data was collected through the semi-structured face-to-face interview from fourteen (14) beneficiaries of social welfare services and five (05) Social workers working for the Department of Social Development at Moroke Social work Office and analysed following Creswell (1998)’s steps of analysis. The study sample size was nineteen (19) respondents which were reached through purposive sampling with non-probability used as a sub-type. The study findings indicate that the implementation on the accessibility of social welfare services is beneficial and improves their social lives of beneficiaries of social welfare services; the level of satisfaction is good concerning the response to the experiences that beneficiaries of social welfare have on the implementation of accessibility of social welfare services, the role of the Department of Social Development when addressing challenges faced by beneficiaries concerning the implementation on the accessibility of social welfare services is not fully prominent, beneficiaries travel a long distance to Moroke office approximately 20 km to access social welfare services; beneficiaries of social welfare services have no support systems while facing the challenges and social workers have limited resources while facilitating the implementation on the accessibility of social welfare services.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Social welfare services; Department of Social Development; Shakung village; Limpopo Province; South Africa; Child welfare; Child welfare workers; Foster home care; Community development; Social service -- South Africa -- Limpopo; Social workers -- South Afriac -- Limpopo